STUDIES ON EXPERIMENTAL THIAMINE DEFICIENCY IN MALE WISTAR RATS: Pharmaceutical Science-Pharmacology - G.BALAJI; O. ANJANEYULU; P. HANUMANNA; B. MANJUNATHA; D.RAVEENDRANATH; K.VIJAYA SUDHAKARA RAO; B.RAMESH (International Journal of Life Science and Pharma Research, 2022)
The present study investigated the Thiamin deficient in male wistar rats. Male albino rats weighing between 150-200 gm were used. They were divided into two groups and allowed to acclimatize to the new environment conditions of our laboratory for one week before use. They had free access to food and water. The standard group animals were received specified diet (Control rats) (C groups). This provides them the essential dietary requirements. The test animals received polished rice and drinking water was made available to animals all the time. The Serum glutamate oxalo acetate transminase (SGOT), Serum glutamate pyruvate transminase (SGPT), Total protein, Albumin, Serum cholesterol Serum Triglycerides Blood urea, Hemoglobin, High density lipoprotein (HDL) and rectal temperature of the rats were determined in serum, body weight and temperature recorded every alternative day. In the present study, the thiamin deficient rats showed the increased levels of SGOT, SGPT, pyruvic acid, total protein, Blood urea Hemoglobin, Serum triglycerides Serum Cholesterol and decreased body weights, HDL, Albumin and rectal temperature when compared with the normal diet received rats. Thiamin deficiency is due to excessive washing of rice, and low intake of fruits and vegetables.